lo g a x 2 y = m and lo g a y / x 3 = n express lo g a x / y in terms of m and n.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
2 nd eqtn is wrong logy - 3logx=n
Log in to reply
thanks for reminding me! but the solution is still the same.
assume (x/y) = k then m = 3logx - logk
& (-n) = logk+ 2logx eliminate logx then solve for K
i am also getting the same answer bt hw it is -2/5m-3/5n
what if we consider x/y = (x^2/y)^2/ (y/x^3) and then take log? hence log(x/y) = 2*log (x^2/y) + log(y/x^3) substituting the value of log (x^2/y) and log(y/x^3) it gives log(x/y) = 2m + n. Where am i wrong ??
I agree to his solution, because that is what i get too
log ax^2+log ay=m is 1 and log ay-log ax^3 is 2. Make log ax and log ay as a subject and use subtitution method. From the equation formed, simplify and you should be getting -2/5m-3/5n.
how do you exactly find that logax^2+logay=m is 1?
I think the answer is only m/2.
I didint get this! :(
good question..
Solution: log(a) x^2 y=m =>log(a) x^2 + log(a) y = m =>2log(a) x+ log(a) y = m ------------- (eq. i)
log(a) y/x^3=n => log(a) y - log(a) x^3 =n =>log(a) y - 3log(a) x =n ----------------- (eq ii)
Subtracting (eq. ii) from (eq. i) we get - 2log(a) x + log(a) y - m + 3log(a) x - log(a) y +n=0 =>5log(a) x = m-n => log(a) x = (m-n)/5
Similarly we get log(a) y = (3m+2n)/5
To find out log(a) x/y i.e. we need to find out log(a) x - log(a) y Therefore, log(a) x - log(a) y = {(m-n)/5} - {(3m+2n)/5} = {m-n-3m-2n}/5 = -2m/5 - 3n/5 (ANS)
Problem Loading...
Note Loading...
Set Loading...
Parse the equations to 2 l o g a x + l o g a y = m and l o g a y − 3 l o g a x = n . After that, use elimination method to find the value of l o g a x and l o g a y . Then, substitute those value to l o g a x / y which has been changed to l o g a x − l o g a y . The answer is 5 − 2 m − 3 n